Physicochemical Properties of Warp Knitted Fabrics Colored with Madder and Gall Oak for Sportswear - PARS, ABDULKADİR (My University, 2024)
Polyamide/elastane warp-knitted fabrics were separately dyed with gall oak (Quercus infectoriaOlivier) and madder (Rubia tinctorumL.). Chromatographic and spectroscopic methods were used to analyze dyed warp-knitted fabrics. A reserved phase high-performance liquid chromatography with the diode-array detection (RP-HPLC-DAD) method was utilized to determine the components of dyes present in the dyed fabrics. Scanning electron microscopy-energy X-ray spectroscopy (SEM-EDX) was utilized for morphological analysis. The undyed and dyed warp-knitted fabrics were characterized by FT-IR. The CIEL*a*b* values of the dyed polyamide-elastane warp-knitted fabrics were measured. Further, in physical testing, the pilling and abrasion resistance of raw and dyed fabrics were examined, and the water contact angle values of all fabrics were measured. Pilling test results were evaluated with a grade of 5 for all fabrics as the best score, and the resistance of fabrics to abrasion was very good. The formation of the fiber-metal-dye complex caused the fabric’s contact angle to drop, giving the fabric a hydrophilic character. The colorfastness characteristics of the dyed fabrics to light, rub, wash, and perspiration have been evaluated. The light fastness scores vary from 3 to 5, and they are satisfactory for using natural dyes to color textiles since they are in the good to moderate range. Overall, the dyed samples displayed a score of 5, which is excellent, on the Gray Scale for washing fastness.

分别用苦栎（Quercus infectioria Olivier）和茜草（Rubia tinctorum L.）对 聚酰胺/弹性纤维经编织物进行染色。采用色谱法和光谱法对经编染色织 物进行了分析. 采用保留相高效液相色谱-二极管阵列检测法（RP-HPLCDAD） 测定染色织物中染料的成分. 利用扫描电子显微镜能量X射线光谱 （SEM-EDX）进行形态分析. 用FT-IR对未染色和染色的经编织物进行了表 征，测定了染色后的聚酰胺-弹性纤维经编织物的CIEL*a*b*值. 此外，在物 理测试中，检查了生织物和染色织物的抗起球性和耐磨性，并测量了所有 织物的水接触角值. 所有织物的起球测试结果都以5分为最佳分数，织物的 耐磨性非常好. 纤维-金属染料复合物的形成导致织物的接触角下降，使织 物具有亲水性. 对染色织物的耐光、耐擦、耐洗、耐汗牢度进行了评价. 耐 光性得分从3到5不等，它们对于使用天然染料给纺织品上色是令人满意 的，因为它们在良好到中等的范围内. 总体而言，染色样品在洗涤牢度的 灰度上显示出5分，这是极好的.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); 经编织物; 茜草; 水接触角; 聚酰胺; HPLC; SEM- EDX; Warp knitted fabrics; madder; water contact angles; polyamide